WD-repeat protein encoding genes among prokaryotes of the Streptomyces genus - Stoytcheva, Z; Joshi, B; Spízek, J; Tichý, P (Folia microbiologica, 2000)
Southern hybridization with probes designed for detection of WD-repeats coding sequences gave positive results in 21 streptomycete strains indicating that WD-repeats encoding genes are massively spread among streptomycetes. One of them, the wdlA gene of Streptomyces lincolnensis, codes for a 971 amino acid protein with seven WD-repeats in its C-terminus, two transmembrane domains and an ATP/GTP binding site upstream of the WD-repeat region.
Keywords: sekvenční seřazení; Blotting, Southern; Membrane Proteins; Sequence Analysis, DNA; Molecular Sequence Data; klonování DNA; molekulární sekvence - údaje; sekvence aminokyselin; ABC transportéry; proteiny vázající GTP; bakteriální proteiny; sekvenční analýza DNA; Amino Acid Sequence; ATP-Binding Cassette Transporters; DNA Probes; Sequence Alignment; repetitivní sekvence aminokyselin; Bacterial Proteins; Southernův blotting; membránové proteiny; Cloning, Molecular; Repetitive Sequences, Amino Acid; GTP-Binding Proteins; Streptomyces; DNA sondy